2007
DOI: 10.1038/sj.npp.1301371
|View full text |Cite
|
Sign up to set email alerts
|

Limbic Activation to Cigarette Smoking Cues Independent of Nicotine Withdrawal: A Perfusion fMRI Study

Abstract: Exposure to cigarette smoking cues can trigger physiological arousal and desire to smoke. The brain substrates of smoking cue-induced craving (CIC) are beginning to be elucidated; however, it has been difficult to study this state independent of the potential contributions of pharmacological withdrawal from nicotine. Pharmacological withdrawal itself may have substantial effects on brain activation to cues, either by obscuring or enhancing it, and as CIC is not reduced by nicotine replacement strategies, its n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
283
3
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 327 publications
(315 citation statements)
references
References 42 publications
28
283
3
1
Order By: Relevance
“…In addition to changes in reward, evidence from both human and animal research has demonstrated that nicotine alters cognitive processes, including associative learning [35,37,48,58,88]. For example, cravings for nicotine were increased following the presentation of previously neutral environmental cues that were associated with smoking [88].…”
Section: Nicotinic Acetylcholine Receptors: Animal Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to changes in reward, evidence from both human and animal research has demonstrated that nicotine alters cognitive processes, including associative learning [35,37,48,58,88]. For example, cravings for nicotine were increased following the presentation of previously neutral environmental cues that were associated with smoking [88].…”
Section: Nicotinic Acetylcholine Receptors: Animal Researchmentioning
confidence: 99%
“…For example, cravings for nicotine were increased following the presentation of previously neutral environmental cues that were associated with smoking [88]. Similarly, withdrawn smokers and non-withdrawn smokers that were exposed to smoking-related stimuli reported increases in cravings [39,48,49]. Research has also demonstrated that contextual cues (i.e.…”
Section: Nicotinic Acetylcholine Receptors: Animal Researchmentioning
confidence: 99%
“…Indeed, human neuroimaging studies show that the prefrontal cortex (orbitofrontal, medial prefrontal, prelimbic/cingulate) and the basolateral amygdala are critical in drug-and cue-induced craving in humans (Franklin et al, 2007). In prefrontal regions (eg, cingulate gyrus and obitofrontal cortex), these changes have been associated with a reduction in striatal dopamine D 2 receptor availability observed in addicted subjects (Heinz et al, 2004;Volkow et al, 1993Volkow et al, , 2001aVolkow et al, , 2007.…”
Section: Ventral Striatum/dorsal Striatum/thalamus: Voluntary To Habimentioning
confidence: 99%
“…Evidence suggests that drugs lead to pathological adaptations in a widely distributed neuronal network divided into four subcircuits: reward/salience (ventral tegmental area (VTA), ventral striatum), motivation/drive/craving (orbitofrontal cortex (OFC), insula), learning/memory (hippocampus, amygdala), and control (dorsolateral prefrontal cortex (DLPFC), anterior cingulate cortex (ACC)) (Volkow et al, 2003(Volkow et al, , 2004Everitt and Robbins, 2005;Naqvi and Bechara, 2009). Smoking cues were found to activate this network in smokers but not in nonsmokers (Brody et al, 2002;Due et al, 2002;David et al, 2005;Smolka et al, 2006;Franklin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%